Enhancing Digital and English Literacy with a Digital Folklore Corner to Promote Talawaan Tourism Village: Meningkatkan Literasi Digital dan Bahasa Inggris melalui Pojok Baca Cerita Rakyat Digital untuk Mempromosikan Desa Wisata Talawaan - Kobis, Dewi Christa; Sigarlaki, Stephani; Tomatala, Michel Farrel; Ali, Eunike Ivana; Montolalu, Mychella (Jurusan Pendidikan Bahasa dan Seni, FKIP, Universitas Mataram, 2025)
This community service aimed to strengthen the community’s capacity and potentials of Talawaan Tourist Village by integrating technology, capacity building, and cultural preservation. The program addressed four main issues: low tourist visits, limited digital literacy, low English proficiency, and declining cultural knowledge. To tackle these issues, the community service program proposed digital literacy training, English for tourism workshops, and establishment of both a 3x4 meter folktale reading corner and a digital e-library at wisatatalawaan.com. A total of twenty participants joined three training sessions, where they learned to create promotional videos, practiced English communication, and practiced managing digital platforms. The program produced both tangible outputs such as the reading corner, books, QR codes and intangible products such as training modules, website, and multimedia content. Community participation was notably high, with community actively enganged in video production, storytelling, and content uploads. The program generated significant impacts that include improved English communication skills, enhanced digital competence, increased visibility of Tunan Waterfall, and strengthen cultural identity. These outcomes are expected to boost tourism, generate economic benefits, and ensure cultural sustainability. Ultimately, the program positions Talawaan as a model for community-based cultural tourism that successfully combines traditional storytelling with digital innovation.